ANALISIS PERBEDAAN VOLUME PERDAGANGAN, HARGA SAHAM DAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT DI BURSA EFEK INDONESIA PERIODE (2004-2008) - SE, M.Si, Ak, Murtini; SE., M.Si, Dewi Purnasari; Tri, Nila (STIE Muhammadiyah Pekalonga, 2011)
Stock split is one kind of corporate action implemented by companies in order to rearrange stock price to be a more liquid rangel and provide more positive signal to investor. The purpose of this research is to analyze the differences of trading volume activity, stock price and abnormal return, so that investors could use this event to gain benefit.This research uses secondary data that collected from Indonesian Capital Market Directory ( ICMD ) 2004 up to 2008, IDX Statistics 2008 and www.idx.co.id. The data used in research were taken from : announcement date of stock split applied as event date ( t 0 ), daily closing price, indeks daily closing of the companies applying stock split within observation period ( IHSG ), the amount of daily traded share and the amount of listed share. There are 49 for this research. They are stocks of the companies which implemented stock split policy within 2004 up to 2008 and which have been listed in BEI.Â Results of the study show that there are no significant difference of Â trading volume activity. There are significant differences of stock price, and abnormal return before and after stock split event.Keyword : stock split, trading volume activity, stock price, abnormal return